Radiatsiia. Linii zashchity - Ponomarev, I. (Soviet Union : Kievnauchfilm Studio, 1987)
Soviet educational propaganda film on nuclear energy.
Start: 00:09:00, End: 00:28:00
With voice-over in Hungarian
Keywords: Soviet Union